2010
DOI: 10.1002/ceat.201000314
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Production of L‐Lysine‐L‐lactate with Fractionated Press Juices from the Green Biorefinery

Abstract: Lactic acid (LA) is a platform chemical for a future bio-based economy. Aminium lactates act as intermediates for the production of lactic acid sequence products like lactide. It could be demonstrated that, after separation of proteins from alfalfa press juice, the supernatant can be used as fermentation media for the production of the aminium lactate, L-lysine-L-lactate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The juices, featuring a variety of nitrogen-containing compounds and inorganic salts, can act as a substitute for synthetic nutrients. 8,9 Already existing processes, like the microbial PHA-production, can become more efficient due to lower feedstock costs. 10 Numerous investigations have been made into alfalfa press juices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The juices, featuring a variety of nitrogen-containing compounds and inorganic salts, can act as a substitute for synthetic nutrients. 8,9 Already existing processes, like the microbial PHA-production, can become more efficient due to lower feedstock costs. 10 Numerous investigations have been made into alfalfa press juices.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that alfalfa press juices can act as a substitute for MRS, a synthetic nutrient, in lactic acid production, cutting processing costs. 8,9,11 Cultivation and Fractionation of Leguminous Biomass for Lactic Acid Production Chemical industries are set to increase the proportion of renewable feedstock in their production in the decades ahead. Green Biorefineries that divide fresh green biomass into cakes and juice deliver valuable products for various industrial uses.…”
Section: Introductionmentioning
confidence: 99%
“…The content of WSC, which is essential for fermentation products, ranges from about 330–450 g kg –1 dm for clover and Italian ryegrass . The lactic acid yield by continuous fermentation of grass‐ or grass silage juices ranges from 0.9 to 1.0 g g –1 WSC …”
Section: Methodsmentioning
confidence: 99%
“…A recent study has demonstrated that, after separation of proteins from alfalfa press juice, the supernatant can be used as fermentation media for the production of the ammonium lactate, L-lysine-L-Lactate, which acts as intermediates for the production of lactic acid sequence products like lactide (Leiß et al 2010). Another study evaluated the possibility of recovery of lactic acid from various grass silages through a two-step process, in which the crude liquid press extract was pre-treated with ultrafiltration membranes followed by purification with mono-polar electrodialysis (Danner et al 2000).…”
Section: Processing Of Press Juice To Value-added Productsmentioning
confidence: 99%